Attitudes toward the pandemic and COVID-19 vaccination intention among German university students and the general population: Results from two cross-sectional surveys - Baldofski, Sabrina; Dogan-Sander, Ezgi; Mueller, Sophia E.; De Bock, Freia; Huebl, Lena; Kohls, Elisabeth; Rummel-Kluge, Christine (Frontiers in Public Health, 2022)
The COVID-19 pandemic has had an impact on nearly all people. Vaccines provide an effective tool to combat the pandemic, however, vaccination hesitancy remains an issue. This study aims to investigate a) students' attitudes towards the pandemic, b) potential differences in attitudes between university students and the general population, and c) to examine predictors of vaccination intention in both samples. In comparison to the general population, university students were significantly more likely to report being worried about/thinking about the coronavirus and to perceive the coronavirus as overrepresented in the media (all p < .001). University students reported a more supportive attitude towards vaccinations in general (students: M = 4.57, SD = 0.85; general population: M = 3.92, SD = 1.27) and a significantly higher vaccination intention (students: n = 4,438, 78.7%; general population: n = 635, 47.7%) than the general population (p < .001). Regression analyses revealed that in university students, vaccination intention was significantly predicted by not having children, a supporting attitude towards vaccinations in general, the belief that the coronavirus is overrepresented in the media, and less thinking about/worrying about the coronavirus (all p < .05). In the general population, vaccination intention was significantly associated with male gender, higher age, not having children, a supporting attitude towards vaccinations in general, and the belief that the coronavirus is overrepresented in the media (p < .05). The qualitative analysis among university students revealed that the most frequently stated positive aspect of the pandemic was to be more flexible due to digitalization (n = 1,301 statements, 22.2%) and the most frequently stated negative aspect was restriction in social life (n = 3,572 statements, 24.2%). The results indicate differences in the attitudes towards the pandemic between university students and the general population. In addition, differences regarding factors associated with vaccination intention were found in both samples. These results could be important to be considered when designing and targeting vaccination campaigns aiming at informing different population or age groups.